Pembinaan Peningkatan Kapasitas Produksi Minyak Sereh Wangi Kelompok Tani Gema Industri - Jefrianus Nino; Maria Magdalena Endah Mulat Satmalawati; Marsianus Fallo; Faustinus Kadha (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2025)
Lemongrass (Cymbopogon nardus. L) is a type of essential oil plant whose essential oil is obtained from the leaves and stems of lemongrass. Lemongrass is classified as a medicinal plant with active compounds that can be used as medicine. The lemongrass oil distillation technique carried out by the Gema Industri farmer group uses the water distillation method. The water distillation method carried out by the Gema Industri farmer group using iron drums can affect the quality of the lemongrass oil produced. An inefficient cooling system (condenser) causes product loss because the components of lemongrass oil are volatile or easily evaporated so that it greatly affects the quality of the distillation results. The purpose of community service is to improve the design of lemongrass oil distillation equipment using a steam distiller made of stainless steel with science and technology input and improve the cooling installation to increase the yield of lemongrass oil. Community service activities are carried out in 4 stages, including socialization, training in preparing raw materials, training in distillation based on stainless steel steam distiller technology and the Bottle Packaging Design Training stage. The use of a steam distiller using a steam method made of stainless steel with a distillation process carried out for 4 hours. The time needed for the oil to come out of the distillation results is 1 hour after the distillation process is carried out. The yield of oil produced is 1.2301%.